2013
DOI: 10.1090/s0002-9947-2013-05957-0
|View full text |Cite
|
Sign up to set email alerts
|

On simplicial resolutions of framed links

Abstract: Abstract. In this paper, we investigate the simplicial groups obtained from the link groups of naive cablings on any given framed link. Our main result states that the resulting simplicial groups have the homotopy type of the loop space of a wedge of 3-spheres. This gives simplicial group models for some loop spaces using link groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…From the construction of d i and s i , it is routine to show that the simplicial identities hold and so G(L; X) is a simplicial group. The main result in [7] showed that the geometric realization of G(L; X) is homotopy equivalent to the loop space of a wedge of 3-spheres for any non-trivial framed link L.…”
Section: Preliminarymentioning
confidence: 99%
See 4 more Smart Citations
“…From the construction of d i and s i , it is routine to show that the simplicial identities hold and so G(L; X) is a simplicial group. The main result in [7] showed that the geometric realization of G(L; X) is homotopy equivalent to the loop space of a wedge of 3-spheres for any non-trivial framed link L.…”
Section: Preliminarymentioning
confidence: 99%
“…( [7]) Suppose L f is a framed link in S 3 with L a trivial knot and the associated naive cabling L n the Hopf link with (n + 1)-components, then the link group G(L; X) = {G(L n )} n 0 is a simplicial group. Furthermore, the geometric realization of G(L; X) is homotopy equivalent to ΩS 3 .…”
Section: The Hopf Fibrationmentioning
confidence: 99%
See 3 more Smart Citations